Global Cosmetics Company Limited / Ami Azida Abdul Aziz - Abdul Aziz, Ami Azida (2021)
Global cosmetics is an OEM ODM Cosmetic Manufacture company based on respect, fun and research about cosmetics, lipsticks and skincare products. As a professional manufacturing leader in the cosmetic industry, their services include bespoke products, private label, personalization, OEM and ODM. This common create beauty products in a highly professional way engaging businesses for overseas retailers, small brands and enterprise. Most importantly, they guide us through the cosmetics. Next, this company also are a manufacture company expert on beauty. Their products include lip care, skincare, toiletries, color cosmetics, fragrance and gift set. As for fragrances, their famous products which is body mist is manufactured with toxin-free materials and safe regulations to be applied directly on the skin preferably after showering or bathing. Much lighter and softer than perfumes are made to hydrate the skin. The level of fragrance concentration of this product is much lighter but the manufacturing still requiring safety procedures. Among all the fragrance products, this is a complementary scent that provides a light and breezy touch to the skin. However, in this company analysis, it is focusing on the body mist that is produces by the Global Cosmetics company to be investigate, identified and analyzed along with their current problems and come out with solutions. The problem regarding to their products is the body mist can’t be a repellent for those people suffering with bugs. Almost everyone these days is familiar with the bug repelling chemical DEET. This amazingly effective ingredients are in many commercial bug sprays and carries the potential risk of unpleasant side effects for humans. Aside from that, the solutions to that problem primarily are to do the innovation of the products. Their Research and Development part should alter their raw materials with a new alternative such as using natural ingredients that also can function as a repellent. This solution is considered to aid Global Cosmetics company in producing very quality product to be served to their customers in order to sustain their business growth, developments and more achievements ahead.